The Influence Of Price, Product Quality, And Promotion On Purchase Decisions At The Shopee Marketplace - Shelly Arnetta; Pujiarti (Fakultas Bisnis, 2023)
This research was conducted to determine the influence of price, product quality and promotion on purchasing decisions on the Shopee marketplace. Quantitative research is the procedure used in this thesis and uses questionnaires to 100 respondents. The results of data processing using SPSS 25 obtained a T table of 1.660, a price T count of 6.868 > 1.660, a product quality T count of 0.075 > 1.660 and a promotion T count of 3.201 > 1.660. The results of hypothesis testing obtained Fcount 91.417>2.70 Ftable and a significance of 0.000 <0.05, meaning that price, product quality and promotion have a simultaneous and significant effect on purchasing decisions on the Shopee marketplace and based on the coefficient of determination test, the adjusted R Square value is 0.733, which means All independent variables influence purchasing decisions by 73.3% and the remaining 26.7% is explained by other factors not explained in this regression analysis.